2018
DOI: 10.1111/nph.15531
|View full text |Cite
|
Sign up to set email alerts
|

Not all sex‐biased genes are the same

Abstract: This article is a Commentary on Sanderson et al., 221: 527–539.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, we infer that tissue-limitation (a more narrow expression domain) is likely more important for shaping reproductive protein evolution specifically, as lower mean gene expression was not significantly associated with higher protein evolution for reproductive genes ( Figure S1, Table 4), and reproductive loci also had much higher mean gene expression levels in comparison to generally-expressed genes and, especially, vegetative loci. High tissue-specificity has been proposed as an important contributor to elevated rates of reproductive protein evolution-and a better predictor of this than sex-biased gene expression per se-in both animals (Meisel 2011) and some plants (Veltsos 2019). For example, in Arabidopsis thaliana and close relatives, Harrison et al (2019) found faster protein evolution in both pollen-specific and tissue-specific sporophytic genes compared to loci expressed in >1 tissue, although pollen-specific loci still retain the highest evolutionary rates in this and other analyses in these species (e.g.…”
Section: 2mentioning
confidence: 99%
“…However, we infer that tissue-limitation (a more narrow expression domain) is likely more important for shaping reproductive protein evolution specifically, as lower mean gene expression was not significantly associated with higher protein evolution for reproductive genes ( Figure S1, Table 4), and reproductive loci also had much higher mean gene expression levels in comparison to generally-expressed genes and, especially, vegetative loci. High tissue-specificity has been proposed as an important contributor to elevated rates of reproductive protein evolution-and a better predictor of this than sex-biased gene expression per se-in both animals (Meisel 2011) and some plants (Veltsos 2019). For example, in Arabidopsis thaliana and close relatives, Harrison et al (2019) found faster protein evolution in both pollen-specific and tissue-specific sporophytic genes compared to loci expressed in >1 tissue, although pollen-specific loci still retain the highest evolutionary rates in this and other analyses in these species (e.g.…”
Section: 2mentioning
confidence: 99%
“…High tissue-specificity has been proposed as an important contributor to elevated rates of reproductive protein evolutionand a better predictor of this than sex-biased gene expression per se-in both animals (Meisel, 2011) and some plants (Veltsos, 2019). For example, in Arabidopsis thaliana and close relatives, Harrison et al (2019) found faster protein evolution in both pollen-specific and tissue-specific sporophytic genes compared to loci expressed in >1 tissue, although pollen-specific loci still retain the highest evolutionary rates in this and other analyses in these species (e.g., Szovenyi et al, 2013;Gossmann et al, 2016).…”
Section: Rates Of Protein Evolution Are Affected By Tissue-specificity But Not Haploid Expressionmentioning
confidence: 99%
“…Similarly, we find little evidence for stronger or more widespread purifying selection on haploid-expressed loci, which would be observed as lower mean rates of protein evolution in gametophytic loci. Stronger purifying selection due to haploid expression has been proposed as one reason why sex-biased loci (generally, pollen expressed loci) do not appear to evolve faster than non-sex-biased loci in several dioecious species (Cossard et al, 2019;Sanderson et al, 2019;discussed in Muyle, 2019; but see also Veltsos, 2019) and, indeed, sometimes appear to evolve more slowly (e.g., Darolti et al, 2018). Our data do not suggest stronger purifying selection in either gametophytic-limited proteins in general, or ovule-and pollen-limited loci specifically, in our species.…”
Section: Rates Of Protein Evolution Are Affected By Tissue-specificity But Not Haploid Expressionmentioning
confidence: 99%
“…In recent years, there have been growing studies on the expression dynamics and molecular evolutionary rates of sexbiased genes in flowering plants, including hermaphroditic Arabidopsis thaliana (Gossmann et al, 2014 ;, Solanum (Moyle et al, 2021 ), and dioecious Silene latifolia (Zemp et al, 2016 ), Salix viminalis (Darolti et al, 2018 ), Mercurialis annua (Cossard et al, 2019 ), Populus balsamifera (Sanderson et al, 2019 ), and Leucadendron (Scharmann et al, 2021 ). However, despite such advances, the molecular evolution pattern of sex-biased genes in plants remains inconsistent among the studied plant species (Muyle, 2019 ;Veltsos, 2019 ). In dioecious plants such as Mercurialis annua and Leucadendron, Cossard et al, (2019) and Scharmann et al, (2021) found no significant differences in evolutionary rates of proteins among female-biased, male-biased and unbiased genes detected between male and female plants leaf tissues, although the expression of sex-biased genes was highly different from unbiased genes in leaves.…”
Section: Introductionmentioning
confidence: 99%